Tophaceous Gout in an Anorectic Patient Visualized by Dual Energy Computed Tomography (DECT) - Christensen, Heidi Dahl (Am J Case Rep, 2016)
Patient: Female, 40 Final Diagnosis: Gout Symptoms: Joint pain Medication: — Clinical Procedure: Dual energy Computed tomography Specialty: Rheumatology OBJECTIVE: Rare co-existance of disease or pathology BACKGROUND: Gout is characterized by deposition of uric acid crystals (monosodium urate) in tissues and fluids. This can cause acute inflammatory arthritis. The 2015 ACR/EULAR criteria for the diagnosis of gout include dual energy computed tomography (DECT)-demonstrated monosodium urate crystals as a new criterion. DECT is a spectral decomposition that permits recognition of different types of tissues based on their characteristic energy-dependent photon attenuation. A positive scan is defined as the presence of urate at articular or periarticular sites. CASE REPORT: We describe a 51-year-old woman known to have anorexia nervosa. During our clinical examination, we detected plenty of tophi on both hands, but no swollen joints. The diagnosis of gout was made by visualizing crystals in a biopsy from a tophus. The first line of treatment was allopurinol, the second line was rasburicase, and the current treatment is febuxostat 80 mg/day, allopurinol 300 mg twice a day, and colchicine 0.5 mg twice a day. The patient has unchanged arthralgia and the size and number of tophi remain the same as before treatment in spite of active treatment for 3 years. Previously the patient had problems with adherence, but now she claims that she follows the proposed treatment. The last plasma urate (P-urate) was 0.57 mmol/L. Following two years of treatment, DECT of hands visualized monosodium urate crystal deposits in the tophi, as seen on the clinical photos, but also crystals in relation to the tendons and soft tissue. CONCLUSIONS: DECT is an imaging modality useful to assess urate crystal deposits at diagnosis of gout and could be considered during treatment evaluation. Lack of adherence to treatment should be considered when P-urate values vary significantly and when DECT scans over years persistently visualize monosodium urate crystals.